Fabry Disease Prevalence in Renal Replacement Therapy in Turkey - Yalin, S.F.; Eren, N.; Sinangil, A.; Yilmaz, V.T.; Tatar, E.; Uçar, A.R.; Sevinç, M. (S. Karger AG, 2019)
Background: Fabry disease (FD) is an X-linked lysosomal storage disorder resulting from lack of alpha-galactosidase A (AGALA) activity in lysosomes. Objective: In this multicenter study, we aimed to evaluate the prevalence of FD in renal transplant (Tx) recipients in Turkey. We also screened dialysis patients as a control group. Methods: All Tx and dialysis patients were screened regardless of the presence of a primary disease. We measured the AGALA activity in all male patients as initial analysis. Mutation analysis was performed in male patients with decreased AGALA activity and in female patients as the initial diagnostic assay. Results: We screened 5,657 patients. A total of 17 mutations were identified. No significant difference was observed between the groups regarding the prevalence of patients with mutation. We found FD even in patients with presumed primary kidney diseases. Seventy-one relatives were analyzed and mutation was detected in 43 of them. We detected a patient with a new, unknown mutation (p.Cys223) in the GLA gene. Conclusions: There are important implications of the screening. First, detection of the undiagnosed patients leads to starting appropriate therapies for these patients. Second, the transmission of the disease to future generations may be prevented by prenatal screening after appropriate genetic counseling. In conclusion, we suggest screening of kidney Tx candidates for FD, regardless of etiologies of chronic kidney disease. © 2019 S. Karger AG, Basel.
Keywords: Alpha-Galactosidase A; Fabry Disease; Family Screening; Index Case; Renal Transplant Recipient